Diversity and community structure of epibenthic invertebrates and fish in the North Sea - Ruth Callaway (ICES Journal of Marine Science, 2002)
The structure of North Sea benthic invertebrate and fish communities is an importantindicator of anthropogenic and environmental impacts. Although North Sea fishstocks are monitored regularly, benthic fauna are not. Here, we report the results of asurvey carried out in 2000, in which five nations sampled the epibenthic and fish faunaat 270 stations throughout the North Sea. The aim of the survey was to investigate thediversity and community structure of epibenthic and fish communities and to identifyrelationships with environmental factors, including the frequency of commercial otterand beam trawling disturbance. Epibenthic species diversity was lower in the southernNorth Sea than in central and northern areas. Fish, conversely, were more diverse inthe south. The 50 m, 100 m and 200 m depth contours broadly defined the boundariesof benthic and fish communities. The abundance of epibenthos of the southern NorthSea was dominated by free-living species, whilst north of the 50 m contour sessilespecies prevailed. A hybrid area, with sessile species typical of the north and free-livingspecies characteristic of the south, was found off the Norfolk and Flamborough coaststretching towards the Dogger Bank.Large-scale hydrodynamic phenomena were most likely to be responsible for themain divisions between communities, especially the boundary between mixed andstratified water masses. However, bottom temperature, sediment parameters and beamtrawling were closely correlated with species richness and diversity, as well ascommunity patterns, and may modify regional species composition.Our study shows that effective large-scale sampling of benthic communities can beconducted during existing fisheries surveys. Since annual fisheries surveys are conductedthroughout the northeast Atlantic shelf seas, concurrent benthic surveys wouldallow benthic sampling on unprecedented spatial and temporal scales. The sampleswould help to monitor the environmental impacts of trawling disturbance, climatechange, pollution and other natural and anthropogenic factors.